An investigation of cephalometric and morphological predictors of successful Twin Block therapy - Fleming Padhraig S.; Qureshi Usman; Pandis Nikolaos; DiBiase Andrew; Lee Robert T. (Sciendo, 2012)
Objective: To identify predictors of overjet reduction, changes in mandibular length (Co-Me) and antero-posterior changes in mandibular position (Pog-Vert) during Twin Block therapy.